Gold shares or krugerrands: Which is the better investment? - J. F. Affleck-Graves; G. D.I. Barr (South African Journal of Business Management, 1986)
In this study we examine the performance of krugerrands vis-à-vis gold shares on the Johannesburg Stock Exchange over the period 1980 - 1983. Using the Markowitz portfolio selection model and Sharpe's capital market theory we are able to demonstrate that over the past few years, krugerrands have produced sub-optimal returns for the South African investor. This follows because in each year the investor would have been better off in some combination of gold shares and treasury bills rather than in krugerrands, no matter what risk level he chose. Furthermore, even in the naive case where the investor merely buys the gold share index, krugerrands are shown to be an inferior investment.
Keywords: 650